BOARD INDEPENDENCE AND CAPITAL STRUCTURE OF NIGERIAN NON-FINANCIAL LISTED FIRMS: THE MODERATING ROLE OF INSTITUTIONAL OWNERSHIP - Abdullahi, Sani; Alifiah, Mohd Norfian (International Journal of Economics, Business and Accounting Research (IJEBAR), 2021)
The Nigerian corporate environment has the potentials for high information asymmetry and less disclosure due to the weak institutional structure and an ineffective market for corporate control. These instances may undermine the monitoring capacity of independent directors in the boardroom. Thus, signifying the need for a complementary corporate governance mechanism to boost investors’ confidence. This research views that institutional investors have the incentives to strengthen board governance, given their sophisticated financial expertise and management skill. Therefore, this paper measures the moderating role of institutional ownership on the relationship between board independence and firms’ capital structure. The study analysed the balanced panel data of 56 Nigerian non-financial listed companies for seven years (2012-2018) using the random effects technique. This study presents evidence that higher levels of institutional ownership strengthen the effect of board independence on the firms’ leverage and vice versa. Hence, the result implies that managers may face stringent monitoring when institutional investors and independent directors interact. Such superior monitoring may compel managers to take on higher leverage to boost firm’ value. Our finding has an important policy implication on enhancing sound corporate governance practices, particularly for firms operating in developing countries where the market for corporate control is ineffective.